Low field magneto-tunable photocurrent in CoFe2O4 nanostructure films for enhanced photoelectrochemical properties - Simrjit Singh (Nature Portfolio, 2018)
Abstract Efficient solar to hydrogen conversion using photoelectrochemical (PEC) process requires semiconducting photoelectrodes with advanced functionalities, while exhibiting high optical absorption and charge transport properties. Herein, we demonstrate magneto-tunable photocurrent in CoFe2O4 nanostructure film under low applied magnetic fields for efficient PEC properties. Photocurrent is enhanced from ~1.55 mA/cm2 to ~3.47 mA/cm2 upon the application of external magnetic field of 600 Oe leading to ~123% enhancement. This enhancement in the photocurrent is attributed to the reduction of optical bandgap and increase in the depletion width at CoFe2O4/electrolyte interface resulting in an enhanced generation and separation of the photoexcited charge carriers. The reduction of optical bandgap in the presence of magnetic field is correlated to the shifting of Co2+ ions from octahedral to tetrahedral sites which is supported by the Raman spectroscopy results. Electrochemical impedance spectroscopy results confirm a decrease in the charge transfer resistance at the CoFe2O4/electrolyte interface in the presence of magnetic field. This work evidences a coupling of photoexcitation properties with magnetic properties of a ferromagnetic-semiconductor and the effect can be termed as magnetophototronic effect.